Error Analysis of College Students’ Paragraph Writing - Astried Damayanti; Sri Utami Dewi; Wawan Prasetyo (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2022)
Errors in writing are often made by the writers. It is commonly occurred to the learners of second language. The research aims to know the college students’ error in writing a paragraph. The researcher focused on finding the errors category and cause of the errors made by the students. The subjects investigated were the students of English Education Study Program of STKIP PGRI Trenggalek who joined Paragraph Writing subject. The design utilized in the research was qualitative research. It was included into content analysis during the data analyzed was the document of students’ writing work. The result of analyzing showed that the errors made by the students could be classified into four categories: omission, additions, misformation and misordering. Meanwhile, the students’ errors were caused both of inter-lingual and intra-lingual. Based on the result of the research, it is recommended to the teacher for learning more about L1 and L2. It is also suggested that the other researcher to conduct research with different design of error analysis